A post-liquefaction study after the 2014 Chiang Rai Earthquake in Thailand - Sethapong Sethabouppha (2018)
© 2018 GEOMATE International Society. A post-liquefaction study at a remote village was conducted after the event of the 6.3 ML2014 Chiang Rai Earthquake in order to investigate the liquefaction condition and to compare liquefaction potential assessment methods for future use. Site surveying, aerial map study, standard penetration test were conducted and found that the subsoil at this site was easily liquefied because the village was lying within abandon river channels with very loose sand layer from the depth of approximately 1 to 6 meters underneath the cohesive soil layer of 1 - 1.5 meter thick at the surface. Four liquefaction potential assessment methods commonly used in the United States and in Japan: 1) modified Seed and Idriss' 1971 method; 2) Idriss and Boulanger (2014); 3) Iwasaki's 1990 method; and 4) Iwasaki's 1996 method were examined. The comparison demonstrates that Iwasaki' 1990 method yielded quite a different result from other three methods with the lowest values of a factor of safety. From this study, other three methods may be considered more favorable.